Achieving the targeted regulation of gamma prime phase in the heterogeneous friction weld of highly alloyed nickel-based superalloy by electric current treatment - Rui Zhan; Qing Liu; Xiaoguang Li; Zixin Zhang; Chunbo Zhang; Wei Guan; Hang Liang; Lei Cui; Yongchang Liu (Materials Research Letters)
This work proposes an innovative targeted regulation approach that leverages the more pronounced thermoelectric effects of electric currents on dense and fine γ’ precipitates in the friction welded joint of highly alloyed nickel-based superalloys, achieving the significant growth of γ’ phases in the weld zone and heat-affected zones, while slight changes in precipitates in the base metal. Corresponding to the growth of γ’ precipitates from 12.28 to 43.16 nm only in the weld, the creep performance of friction welds significantly improved from 12.9 to 99.3 h. Detailed characterizations highlight that the remarkably targeted regulation effect is ascribed to the increased electron scattering rate caused by dense γ’ precipitates, which enhanced local thermal effects and induced high-density currents between the precipitates, collectively promoting element diffusion and corresponding γ’ precipitate growth.